Contribution And Innovation Of Pandang Panjang Muhammadiyah Islamic Boarding School In Development Of Education - Lainah; Iswantir (CV. AFDIFAL MAJU BERKAH, 2022)
Padang Panjang is one of the central cities of Islamic education which has historical resources and heritage that need to be explored and preserved to enrich the treasures of Indonesian history, especially the historical treasures of West Sumatra. During the second wave of the Islamic reform movement in Minangkabau, Padang Panjang was a city that was very influential in the movement. The figures of the Islamic reform movement at that time included DR.H. Abdullah Muhammad, Sheikh Muhammad Jamil Jambek and DR. H. Abdul Karim Amrullah. They realized that the education system of traditional religious schools and the education system of the Dutch East Indies was not in accordance with the conscience of the Minangkabau people. Society demands the establishment of modern schools but there are Islamic religious lessons. This was not fulfilled by the Dutch East Indies government or the traditionalists. In June 1926, the first Muhammadiyah Association was legalized in West Sumatra, precisely in the city of Padang Panjang. One of the most prominent early developments of Muhammadiyah in West Sumatra was the field of education. This can be proven from the requirements given to each branch or branch that wants to get ratification, it must first establish a school. The spread of various schools established by Muhammadiyah shows the magnitude of the efforts made by this reforming organization in the field of education. In the early days of its formation, Muhammadiyah in West Sumatra tended to build public schools at the primary to secondary level with the aim of providing equal distribution of education for as many indigenous people as possible